Anthropogenic nitrogen deposition alters growth responses of European beech (Fagus sylvativa L.) to climate change. (February 2018) - Hess, Carsten; Niemeyer, Thomas; Fichtner, Andreas; Jansen, Kirstin; Kunz, Matthias; Maneke, Moritz; von Wehrden, Henrik; Quante, Markus; Walmsley, David; von Oheimb, Goddert; Härdtle, Werner
Abstract: Global change affects the functioning of forest ecosystems and the services they provide, but little is known about the interactive effects of co-occurring global change drivers on important functions such as tree growth and vitality. In the present study we quantified the interactive (i.e. synergistic or antagonistic) effects of atmospheric nitrogen (N) deposition and climatic variables (temperature, precipitation) on tree growth (in terms of tree-ring width, TRW), taking forest ecosystems with European beech ( Fagus sylvatica L.) as an example. We hypothesised that (i) N deposition and climatic variables can evoke non-additive responses of the radial increment of beech trees, and (ii) N loads have the potential to strengthen the trees' sensitivity to climate change. In young stands, we found a synergistic positive effect of N deposition and annual mean temperature on TRW, possibly linked to the alleviation of an N shortage in young stands. In mature stands, however, high N deposition significantly increased the trees' sensitivity to increasing annual mean temperatures (antagonistic effect on TRW), possibly due to increased fine root dieback, decreasing mycorrhizal colonization or shifts in biomass allocation patterns (aboveground vs. belowground). Accordingly, N deposition and climatic variables caused both synergistic and antagonistic effects on the radial increment of beech trees, depending on tree age and stand characteristics. Hence, the nature of interactions could mediate the long-term effects of global change drivers (including N deposition) on forest carbon sequestration. In conclusion, our findings illustrate that interaction processes between climatic variables and N deposition are complex and have the potential to impair growth and performance of European beech. This in turn emphasises the importance of multiple-factor studies to foster an integrated understanding and models aiming at improved projections of tree growth responses to co-occurring drivers of global change. Graphical abstract: Combined effects of nitrogen (N) deposition and annual mean temperature on tree-ring width (RWI) of European beech ( Fagus sylvatica L.) are non-additive: Radial increment is enhanced by increasing annual mean temperature under low N deposition, but significantly reduced under high N deposition. Image 1 Highlights: Interactions of global change drivers on ecosystem functions are poorly understood. Nitrogen pollution and climate change can non-additively affect forest growth. Nitrogen deposition increases the trees' sensitivity to increasing temperatures. Interaction processes of global change drivers are complex and difficult to predict. Multiple-factor studies help to better predict global change effects on ecosystems. Abstract : The present study shows that interaction effects of global change drivers such as climate change and nitrogen pollution non-additively affect tree growth and have the potential to impair performance and services of European beech forest ecosystems.